A framework to improve lean implementation by review leveraging aspects of organisational culture: the case of Saudi Arabia. (26th June 2019) - Alkhoraif, Abdullah A.; McLaughlin, Patrick; Rashid, Hamad
Organisational culture is one of the most important factors to focus on to facilitate the implementation of lean within Saudi Arabian manufacturing. Thus, this article focuses on contributing to develop a framework to improve lean implementation into small and medium enterprise manufacturing organisations in Saudi Arabia by leveraging aspects of organisational culture. Qualitative research is confirmed to be useful for uncovering such insider views on qualitative and grounded theory inside action research with and an inductive approach. The proposed framework aimed to facilitate lean implementation by leveraging aspects of organisational culture. A series of interventions developed with participants. The planned interventions for SMEs are should take place together as a series of interlinked interventions. The contributions of this study are threefold: First, no previous framework of Lean implementation in SMEs, to knowledge about the failure of lean implementation. Finally, it supports the academic society with scheme for proposal future research